Individual and global social responsibility levels of social studies pre-service teachers in terms of different variables - Melek Körükcü; Zafer Tangülü (International Journal of Evaluation and Research in Education (IJERE), 2021)
The purpose of this research was to determine the individual and global social responsibility levels of social studies pre-service teachers in terms of different variables. The research was in survey model. The study group of the research consisted of 179 pre-service teachers who studied at Social Studies Teaching Program in the Faculty of Education at Niğde Ömer Halisdemir University, Turkey in the 2019-2020 academic year. Data collection tools used in the study are a Demographic Information Form developed by the researcher, Individual Social Responsibility Scale and Global Social Responsibility Scale. The data were analyzed through SPSS 20. The results of the study showed that the social studies teacher candidates' levels of individual social responsibility are high while those of global social responsibility are at medium level. It is also found that there is a significant difference in the individual and global social responsibility levels in terms of gender in favor of female pre-service teachers while there is no significant difference in terms of age variable. Also, the results show that the individual and social responsibility levels of pre-service teachers who have foreign friends are higher than those who do not have foreign friends. Another result of the study is that individual social responsibility levels predict social responsibility levels.